1993
DOI: 10.3109/08990229309028845
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Sympathetic Nerve Sprouting in the Rat Cornea Following Neonatal Administration of Capsaicin

Abstract: Corneal sensory and sympathetic nerves exert opposing actions on corneal mitogenesis and wound healing. The mechanisms by which these nerves exert their actions are unknown; however, the release of axonally transported neuropeptides has been postulated. In the present study, we investigated changes in innervation densities of calcitonin gene-related peptide (CGRP-) and tyrosine hydroxylase (TH-)immunoreactive (IR) nerves of the rat cornea following neonatal capsaicin administration, and the relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 59 publications
4
26
1
Order By: Relevance
“…The paucity of these nerve fibers in the central cornea does not necessarily indicate the absence of fibers because it has previously been shown to be richly innervated with peptidergic nerve fibers 17) . The innervation pattern of PGP-and CGRP-IR nerve fibers in the present study is in accord with that observed in previous reports 5,6,[15][16][17]19) . Dense innervation of PGP-IR nerve fibers was demonstrated in whole mount corneas from rat pups (age, <14 days) 6) and cryostat-sections of canine 19) corneas.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The paucity of these nerve fibers in the central cornea does not necessarily indicate the absence of fibers because it has previously been shown to be richly innervated with peptidergic nerve fibers 17) . The innervation pattern of PGP-and CGRP-IR nerve fibers in the present study is in accord with that observed in previous reports 5,6,[15][16][17]19) . Dense innervation of PGP-IR nerve fibers was demonstrated in whole mount corneas from rat pups (age, <14 days) 6) and cryostat-sections of canine 19) corneas.…”
Section: Resultssupporting
confidence: 93%
“…The innervation pattern of PGP-and CGRP-IR nerve fibers in the present study is in accord with that observed in previous reports 5,6,[15][16][17]19) . Dense innervation of PGP-IR nerve fibers was demonstrated in whole mount corneas from rat pups (age, <14 days) 6) and cryostat-sections of canine 19) corneas. In these studies, the nerve fibers formed a network from the corneal center to the corneoscleral limbus, comprising a complex anastomotic meshwork of small-, medium-, and large-diameter nerve bundles.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They also demonstrated a significant increase in the intraepithelial nerve fiber density at 7-9 weeks after treatment (100 mg/kg, i.p) compared with controls (Ogilvy et al, 1991). In spite of the complete disappearance of CGRP-ir subepithelial nerve fibers by 48 h in the capsaicintreated corneas (150 mg/kg, i.p), they increased markedly between 3 and 6 weeks (Marfurt et al, 1993). Thus, it is a common finding that the corneal nerve fibers first decrease and later regenerate (sprouting) during survival periods.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the reduction of wiping is closely related to the decrease of capsaicin-sensitive, corneal PGP-ir nerve fibers. Marfurt et al (1993) reported the decrease of PGP-ir subepithelial corneal nerves of the rat in the whole mount preparations 5, 7 and 10 days later of neonatal capsaicin injection. They argued that the remained nerve fibers may be sympathetic or capsaicin-insensitive corneal nerves.…”
Section: Discussionmentioning
confidence: 99%